2011
DOI: 10.1139/e10-093
|View full text |Cite
|
Sign up to set email alerts
|

Eocene rotation of the Coast Plutonic Complex and Intermontane Belt: paleomagnetism of Eocene plutons along the Klondike Highway

Abstract: Paleomagnetic results are reported for the *59 Ma Skagway, *54 Ma Fraser, *53 Ma Summit Lake, and *48 Ma Clifton felsic plutons of the eastern Coast Plutonic Complex (CPC) that outcrop along the south Klondike Highway in Alaska and British Columbia. Thermal and alternating field step demagnetizing methods yielded stable characteristic remanent magnetization (ChRM) directions for all 29 sites of normal, reversed, and mixed polarity. The ChRM resides in single or pseudosingle domain magnetite and (or) pyrrhotite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…Thus, Symons et al (2005) concluded that the YTT was either autochthonous or para-autochthonous by ∼100 Ma and was simply displaced northwestwards on the Tintina fault zone by ∼5 • (550 km) whereas the IMB was an allochthonous thin-skin belt of terranes on the YTT that underwent 8.3 • ± 7.0 • of northwestward translation (920 ± 775 km) and 35 • ± 14 • of clockwise rotation between ∼102 and ∼54 Ma as well as a further 16 • ± 6 • of clockwise rotation since ∼54 Ma. Subsequently, Symons et al (2009Symons et al ( , 2011 have shown that the YTT and IMB have generated very different incompatible APWPs for the past 200 Ma with the YTT path falling close to the North American path and the IMB path being widely divergent Table 2 • from the North American path from Early Jurassic at least to the Neogene. Three more recent paleomagnetic studies relate to the SAYBIA model of Johnston (2001Johnston ( , 2008.…”
Section: Previous Estimates Of Ytt Motionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, Symons et al (2005) concluded that the YTT was either autochthonous or para-autochthonous by ∼100 Ma and was simply displaced northwestwards on the Tintina fault zone by ∼5 • (550 km) whereas the IMB was an allochthonous thin-skin belt of terranes on the YTT that underwent 8.3 • ± 7.0 • of northwestward translation (920 ± 775 km) and 35 • ± 14 • of clockwise rotation between ∼102 and ∼54 Ma as well as a further 16 • ± 6 • of clockwise rotation since ∼54 Ma. Subsequently, Symons et al (2009Symons et al ( , 2011 have shown that the YTT and IMB have generated very different incompatible APWPs for the past 200 Ma with the YTT path falling close to the North American path and the IMB path being widely divergent Table 2 • from the North American path from Early Jurassic at least to the Neogene. Three more recent paleomagnetic studies relate to the SAYBIA model of Johnston (2001Johnston ( , 2008.…”
Section: Previous Estimates Of Ytt Motionmentioning
confidence: 99%
“…These Figure 8. Schematic showing restored locations for the exposed Yukon-Tanana Terrane and Intermontane Belt terranes in Yukon as proposed by (a) Johnston (2001,2008) at 85 and 45 Ma in the SAYBIA tectonic model, and (b) Symons et al (2005Symons et al ( , 2009Symons et al ( , 2011. Option (a) proposes that the YTT and IMB were a coherent part of a 'ribbon' continent that was translated northwards off North America's western margin by ∼18 • of paleolatitude between ∼85 and ∼45 Ma to accrete in its present location.…”
Section: Imb Tectonics and Remanencementioning
confidence: 99%
See 1 more Smart Citation